The case of literature : forensic narratives from Goethe to Kafka - Höcker, Arne (Signale (Ithaca, N.Y.), 2020)
"This book shows that narrative literature beginning in the late 18th century works out a mode of representing individual cases that exceeds singularity and novelty but stops short of generality and moral didacticism. Two essential questions guide the author's work here: How does this new literature contribute to the establishment of casuistic forms that since the 18th century have been involved in the formation of psychological knowledge and legal decision making? And how, inversely, does the case history contribute to the formation of literary and aesthetic discourses? In answering these questions for the German-language canon, this book contributes to the understanding of how we came to attribute to literature special formative and critical qualities that until today define our cultural self-conception"--